Application of functionalized carbon dots in detection, diagnostic, disease treatment, and desalination: a review. (25th May 2020) - Ehtesabi, Hamide; Amirfazli, Mehdi; Massah, Fatemeh; Bagheri, Zeinab
Abstract: Particularly in recent years, fluorescence carbon dots (CDs) were in the central point of scientist's focus. However, some difficulties may exist concerning CDs. For example, their targeting by other analytes usually goes wrong due to the absence of specific recognition groups on the surface of CDs. Furthermore, due to low quantum yield, they cannot be conducive to bioimaging. Additionally, they do not have biological functionality that originated from poor interaction with biological agents. For improvement of the luminescence properties and extending of new applications for CDs, the functionalisation of CDs has attracted many interests. Functionalised CDs have promising applications. The present paper has reviewed different published reports considering applications of functionalised CDs. In this comprehensive article, first the functionalisation mechanisms of CDs are discussed. Then, the functionalised CDs for detection applications including biochemical and chemical detections are reviewed. After that, functionalised CDs for diagnostic applications are reviewed. In this part functionalised CDs for fluorescence imaging probes, functionalised CDs for surface-enhanced Raman scattering (SERS) imaging and functionalised CDs for photoacoustic imaging probes are discussed. Later, functionalised CDs for disease treatment including drug delivery and photothermal therapy applications are reviewed to elucidate the importance of their function in cancer treatment. Finally, the applications of functionalised CDs for water desalination are reviewed.